2012
DOI: 10.21608/jpp.2012.85375
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and Combining Ability in Watermelon Hybrids

Abstract: This study was carried out to produce promising hybrids of watermelon. Five lines i.e. Line 1 = L 84; Line 2 = L 85 ; Line 3 = L 94 ; Line 4 = L 84g and Line 5 = L 63 were used as female parents and crossed with four cultivars i.e. Tester 6 = Crimson sweet , Tester 7 = Charleston Gray, Tester 8 = Sugar Baby , and Tester 9 = Giza1 as male parents (testers) using a factorial mating design ,in the summer season of 2010.Twenty hybrids and their nine parents (five lines and four testers) were evaluated at the Sakha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…On the other hand, the best cross for Internode length was P 1 xP 3 (3.04 cm) which less than all parents and P 1 xP 2 for leaf area (642.22 cm 2 ). These finding agree with those obtained by El-Gendy (1999), Gabr (2003), Sadek (2003), Abdein (2005), Refai and Mohamed (2009), Moualla et al (2011), Omran et al (2012), Mohan et al (2012).…”
Section: Vegetative Traitssupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the best cross for Internode length was P 1 xP 3 (3.04 cm) which less than all parents and P 1 xP 2 for leaf area (642.22 cm 2 ). These finding agree with those obtained by El-Gendy (1999), Gabr (2003), Sadek (2003), Abdein (2005), Refai and Mohamed (2009), Moualla et al (2011), Omran et al (2012), Mohan et al (2012).…”
Section: Vegetative Traitssupporting
confidence: 91%
“…As well as, the values of crosses ranged from 15.68 (P 1 xP 3 ) to 20.16 mg/100g (P 2 xP 3 , P 3 xP 1 ) for ascorbic acid content, 4.19 (P 2 xP 3 ) to 5.95% (P 1 xP 2 ) for total soluble solids, 5.79 (P 2 xP 3 ) to 7.00 % (P 1 xP 2 ) for dry weight of fruit, 11.40 (P 1 xP 2 ) to 13.00 (P 3 xP 2 ) for fruit number per plant and 1.12 (P 1 xP 2 ) to 1.32 kg (P 3 xP 2 ) for fruit yield per plant. Many investigators, El-Gazzar (1981), El-Gendy (1999), Abd El-Hadi et al (2001), El-Lithy (2002), Gabr (2003), Sadek (2003), Abdein (2005), Refai and Mohamed (2009), Ghobary and Ibrahim (2010), Shamloul and Askar (2011), Moualla et al (2011), Feyzian et al (2009), Omran et al (2012), Jahan et al (2012) and Mohan et al (2012) found highly significant differences among squash genotypes for these traits.…”
Section: Yield and Its Componentmentioning
confidence: 99%
“…At the same time, it could be confirmed that the most crosses for all studied yield and its component traits gave the better mean values over the commercial cultivars resulted in the hybrid vigor that caused by the maximum values for new lines comprised in these crosses in the both seasons. Many investigators, El-Gendy (1999), Abd El-Hadi et al (2001), El-Lithy (2002), Gabr (2003), Sadek (2003), Abdein (2005), Feyzian et al (2009), Refai and Mohamed (2009), Ghobary and Ibrahim (2010), Moualla et al (2011), Shamloul and Askar (2011), Jahan et al (2012), Mohan et al (2012), Omran et al (2012), El-Gazzar et al (2015), Habiba et al (2015), Nada (2015), El-Shoura and Abed (2018) and Elias et al (2020) found highly significant differences among squash genotypes for these traits.…”
Section: Yield and Its Components:-mentioning
confidence: 99%